STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU LEMBAGA PENDIDIKAN DI SMP YIMI GRESIK - Muhammad Arif Syihabuddin (Institut Keislaman Abdullah Faqih Gresik, 2021)
Abstrak: This study describes the implementation of human resource development strategies in improving the quality of educational institutions. Human resource development is very necessary because it has an important aspect for improving the quality of educational institutions. This research was conducted at YIMI Gresik Junior High School using qualitative methods. Data were obtained through interview, observation, and documentation techniques. Data analysis is carried out by condensing data, presenting data, and verifying data. Then the validity of the data is checked by looking at the degree of trust (credibility), transferability (transferability), dependability (dependability) and certainty (confirmability). The results of this study explain that the implementation of the Human Resource Development Strategy in improving the quality of educational institutions at YIMI Gresik Junior High School is carried out through seminars, coaching, and academic supervision programs. The seminar program is implemented through independent and cooperative development programs, independent development includes: seminars and training, while cooperative development includes: school program workshops; IHT; and MGMP. The coaching program is carried out through an intensive development program. The form of these coaching activities is carried out by school principals and school supervisors. While academic supervision is carried out through an intensive program and the principal follows the learning process in the classroom when the teacher teaches by adjusting the schedule of supervision activities that have been set.Kata Kunci: Human Resource Development, Quality of Educational Institutions.